Pembentukan Kecerdasan Spiritual Melalui Kegiatan Ekstrakurikuler Keagamaan - Wahid Khoirul Anam (DIMAR: Jurnal Pendidikan Islam, 2021)
his study discusses the formation of spiritual intelligence through religious extracurricular activities at MTs Nurul Huda Banjar Agung Mataram, the purpose of this research is to make students aware of who they are and how they give meaning to their lives, increase their confidence, make them personally responsible, and form character. This research is a qualitative research whose research location is at MTs Nurul Huda Banjar Agung Mataram. Data collection techniques using observation sheets and interview guidelines. The results of this study indicate that: Efforts to form spiritual intelligence at MTs Nurul Huda Banjar Agung Mataram through three forms including spiritual enlightenment, habituation, and example. The implementation of religious extracurricular activities at MTs Nurul Huda Banjar Agung Mataram as an effort to form students' religious spiritual intelligence, namely by carrying out a program of reading and writing the Qur'an, reading the prophet's prayer, Islamic boarding school lightning and the implementation of Duha prayer and Dhuhur prayer in congregation.